The Role of the Matrix Metalloproteinase-9 Gene in Tumor Development and Metastasis: A Narrative Review - Kalali, Datis (Global Medical Genetics, 2023)
Matrix metalloproteinase-9 (MMP-9) is one of the widely studied enzymes of the extracellular matrix which can degrade various matrix biomolecules. The gene coding for this enzyme has been found to be associated with various multifactorial diseases, including cancer. More specifically, the expression of MMP-9 and polymorphisms of its gene have been found to be correlated with the formation and the invasiveness of different types of cancer. Hence, the latter gene can potentially be used both as a clinical genetic marker and a possible target in anticancer therapy. The present minireview explores the role of the MMP-9 gene in the process of tumor formation, growth, and metastasis and presents an overview of the polymorphisms of the gene associated with cancer as well as its regulation mechanisms, to provide an insight into the potential clinical applications. Nevertheless, further clinical trials and research are still required to reach more valuable conclusions for the clinical implications of the recent findings.
Keywords: matrix metalloproteinases; MMP-9; carcinogenesis; metastasis; oncogenes